Model Draft Regulation on Cryptocurrency in India - Nikam, Rahul J. (Hasanuddin Law Review, 2018)
This article looks at the application of present Indian payment system policies and regulatory model on virtual-currency in India. In fact, simply banning cryptocurrency in India would not serve the purpose of legislature and Reserve Bank of India (RBI); rather it will boost cryptocurrency frauds in India due to absence of any law. The present article analysis shows that there is an ample scope within the present models and policies with necessary amendments to facilitate the regulation of virtual-currency in India. The analysis also suggests new model regulation on cryptocurrency which shall constitute the basic model regulations in India to govern cryptocurrency technology and products. Author uses the Banking Regulation Act as a model, regulating all types of new fintech products such as cryptocurrency, Bitcoin & business activity, its intermediaries, exchanges, customer protection in robust and transparent fashion in India.